HACIA UNA DEFINICIÓN LINGÜÍSTICA DEL TÓPICO LITERARIO - Escobar, Ángel (Myrtia, 2000)
In view of the very different and even contradictory current uses of tópos in the field of literary criticism, my paper proposes to establish a valid definition of this old rhetorical and philosophical term, which very soon pervaded literature, being characterized essentially as the normal version of a literary argument, having both a trópos -function and also the possibility of receiving an antithetical treatment (marked term of the opposition).